2007
DOI: 10.1080/07315724.2007.10719606
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Actions of Phenolic Compounds Found in Dietary Plants on Low-Density Lipoprotein and Erythrocytes in Vitro

Abstract: In view of their protective effects on LDL and erythrocytes against oxidative damage, these phenolic compounds might have potential applications in prooxidant state-related cardiovascular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 39 publications
1
33
2
Order By: Relevance
“…Furthermore, relatively lower MDA concentrations of the test samples, compared to the control ones, at the given time intervals, revealed that lipid peroxidation was retarded by the three plant extracts in relation to their corresponding concentrations. The present findings are in concord with the report of Lam et al [46] . They noted that gamma sickle erythrocytes must have contributed to the poor and insignificant capacities of the three plant extracts to reduce the levels of erythrocyte Met.Hb%.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, relatively lower MDA concentrations of the test samples, compared to the control ones, at the given time intervals, revealed that lipid peroxidation was retarded by the three plant extracts in relation to their corresponding concentrations. The present findings are in concord with the report of Lam et al [46] . They noted that gamma sickle erythrocytes must have contributed to the poor and insignificant capacities of the three plant extracts to reduce the levels of erythrocyte Met.Hb%.…”
Section: Discussionsupporting
confidence: 90%
“…www.antiox.org irradation-induced oxidative stress indicators were significantly reduced in rats after orally administered with Aloe vera. Prevoius findings have attributed the capacities of Zingiber officinale, Aloe vera and Rheum rhabarbarum extracts to reduce lipid peroxidation to the presence of phenolic compounds in these plants [46,62] . Also, membrane protective activities of diverse plant extracts have been attributed to their antioxidant content and capacity to impede membrane lipid peroxidation [47,63,64] .…”
Section: Wwwantioxorgmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in TBARS formation with the extract samples (seed, skin, and juice) compared to the control group without extract is almost 12%. A number of studies have demonstrated that the treatment of erythrocyte membrane with H 2 O 2 results in peroxidation and disruptions of their structures and functions, including changes in ATPase activity and membrane fluidity (32,33). Many pathophysiological events such as inflammation, aging, and ischemia/reperfusion are attributed to this peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Barbaloin protected Ca 2+ -ATPase and protein sulfhydryl groups on erythrocyte membranes against oxidative attack by tBHP/hemin [9] . Effect of barbaloin on nitric oxide (NO), tumour necrosis factoralpha (TNF-alpha) and interleukin were investigated and found significant inhibitory potential.…”
Section: Antioxidant and Anticancer Activitymentioning
confidence: 99%